OCA adhesive material, preparation method thereof and application of OCA adhesive material in preparation of OCA adhesive film
By using OCA glue materials containing acrylic polymers, isocyanate curing agents, functional monomers and photoinitiated radical initiators in the full bonding technology, the problems of overflow, process complexity and high cost are solved, and a high-performance OCA glue film is achieved.
Patent Information
- Application Number
- CN202411993777.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-15
AI Technical Summary
The prior art has problems such as glue spilling, complex process flow, high cost and low yield in full bonding technology, especially when dealing with bubble problems caused by ink segment difference, UV polymerization technology performs poorly.
An OCA glue material is provided, whose components include an acrylic polymer, an isocyanate curing agent, a functional monomer and a photoinitiating radical initiator, and the molecular weight and degree of crosslinking of the polymer are adjusted by adding a chain transfer agent in the preparation of the acrylic polymer.
It has achieved high strength and is not easy to overflow at room temperature, good fluidity and high filling rate at high temperature, and has excellent performance in bonding, coating overflow, thermal disassembly integrity, die-cutting and stamping, which solves the technical shortcomings in the use of OCA films in the prior art.
Smart Images

Figure CN119823682A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of optical adhesives, and in particular to an OCA adhesive material and a preparation method thereof, and application in the preparation of an OCA adhesive film. Background Art
[0002] With the continuous development of display technology, full bonding technology, as an advanced screen assembly process, has attracted much attention because it can significantly improve display effects and durability. Full bonding technology uses optically clear adhesive (OCA) tape to tightly combine the cover plate (which can be made of glass, polyethylene terephthalate PET, polycarbonate PC or cycloolefin copolymer and other materials) with the display module, achieving high definition and high contrast effects while ensuring the compactness of the structure and effective isolation from external interference. The application of this technology makes the screen more beautiful and has a better visual experience.
[0003] However, the implementation of full bonding technology is not easy. It requires complex process flow, high cost investment, and strict requirements on the production environment. For example, parameters such as temperature and humidity must be controlled within a specific range. In addition, once a problem occurs in the full bonding process, rework is very difficult, which further increases the manufacturing cost and production cycle. These factors have limited the widespread application and promotion speed of full bonding technology to a certain extent.
[0004] Ultraviolet (UV) polymerization technology is a commonly used curing method. Although it can complete the curing process in a short time, it has high requirements for monomer purity and equipment precision, which makes OCA tape prone to overflow in actual applications, thus affecting the quality of the final product. Especially when dealing with the bubble problem caused by ink step difference, the performance of UV polymerization technology is not ideal. On the other hand, although solution polymerization technology has advantages in raw material selection and molecular weight control, the OCA film layer in most OCA tapes used for rework on the market still adopts a three-layer structure. Although this structure can meet certain performance requirements, it also brings problems such as complex process flow, high cost and low yield. At the same time, the traditional single-layer OCA has difficulties in diamond wire feeding during hot removal and cannot maintain the integrity of the film after hot removal. This is because the effect of hydrogen bonds is weakened at high temperatures, and the adhesion between OCA and the object is reduced.
[0005] In view of this, the present invention is proposed. Summary of the invention
[0006] One of the purposes of the present invention is to provide an OCA adhesive material to at least solve one of the technical problems existing in the prior art. The OCA adhesive material provided by the present invention has excellent adhesive overflow performance.
[0007] A second object of the present invention is to provide a method for preparing an OCA adhesive.
[0008] The third object of the present invention is to provide an OCA adhesive material or the application of the preparation method in the preparation of OCA adhesive film.
[0009] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0010] In a first aspect, the present invention provides an OCA adhesive material, the components of which include an acrylic polymer, and at least two components selected from the group consisting of an isocyanate curing agent, a functional monomer, and a photoinitiated free radical initiator;
[0011] The components of the acrylic polymer include reactive diluent monomers, acrylic polar monomers, chain transfer agents and thermally initiated free radical initiators.
[0012] Further, the weight average molecular weight of the acrylic polymer is 10,000-900,000, preferably 50,000-400,000;
[0013] Preferably, the glass transition temperature of the acrylic polymer is -30 to 30°C, preferably -20 to 0°C;
[0014] Preferably, the shear strain rate of the acrylic polymer is 0.0010-0.60;
[0015] Preferably, the creep compliance of the acrylic polymer is 0.000001-0.001.
[0016] Furthermore, the acrylic acid polymer comprises the following components by weight:
[0017] 60-80 parts of active diluent monomer, 10-40 parts of acrylic polar monomer, 0.01-5 parts of chain transfer agent and 0.1-5 parts of thermally initiated free radical initiator.
[0018] Further, the chain transfer agent includes at least one of pentaerythritol triacrylate and dipentaerythritol hexaacrylate;
[0019] Preferably, the acrylic polar monomer includes at least one of (meth)acrylamide, N-methyl(meth)acrylamide, N,N-dimethyl(meth)acrylamide, N,N-diethylaminoethyl(meth)acrylate, N,N-dimethylaminoethyl(meth)acrylamide, hydroxyethyl acrylate and N-vinylcaprolactam;
[0020] Preferably, the reactive diluent monomer includes at least one of 2-ethylhexyl acrylate, lauryl acrylate, benzyl acrylate, isobornyl acrylate, tetrahydrofurfuryl acrylate, ethoxyethoxyethyl acrylate and allyl 2-ethylbutyrate;
[0021] Preferably, the thermally initiated free radical initiator comprises at least one of azobisisobutyronitrile, azobisisoheptanenitrile and dibenzoyl peroxide.
[0022] Furthermore, the components of the acrylic polymer also include a solvent;
[0023] Preferably, the solvent comprises at least one of toluene, ethyl acetate, n-butyl acetate, acetone, butanone, isophorone, cyclohexanone, methanol and isopropanol.
[0024] Furthermore, the OCA adhesive material further comprises the following components by weight:
[0025] 100 parts of acrylic polymer, 0.01-3 parts of isocyanate curing agent, 0.0001-2 parts of functional monomer and 0.01-5 parts of photoinitiator free radical initiator.
[0026] Further, the isocyanate curing agent includes at least one of diphenylmethane diisocyanate, toluene diisocyanate, dicyclohexylmethane-4,4'-diisocyanate, tetramethyl-m-xylylene diisocyanate, isocyanoethyl (meth)acrylate and isocyanate ethyl acrylate;
[0027] Preferably, the functional monomer includes at least one of 1,6-hexanediol diacrylate, tripropylene glycol diacrylate, neopentyl glycol diacrylate, tricyclodecane dimethanol diacrylate, ethoxylated trimethylolpropane triacrylate, propoxylated glycerol triacrylate and trimethylolpropane triacrylate;
[0028] Preferably, the photoinitiator free radical initiator is at least one of 1-hydroxy-cyclohexyl-phenyl ketone, 2-methyl-2-(4-morpholinyl)-4'-(methylthio)propiophenone, а,а-dimethyl-а-phenylacetophenone, 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone and 1-hydroxycycloethylphenylacetone.
[0029] In a second aspect, the present invention provides a method for preparing the OCA adhesive, comprising the following steps:
[0030] The acrylic polymer, isocyanate curing agent, functional monomer and photoinitiator free radical initiator in the formulated amount are mixed and then irradiated with ultraviolet light to prepare the OCA adhesive material.
[0031] Furthermore, the acrylic acid polymer is prepared by the following steps:
[0032] The acrylic polymer is prepared by mixing the reactive diluent monomer, the acrylic polar monomer, the chain transfer agent and the thermally initiated free radical initiator in the formulated amount.
[0033] In a third aspect, the present invention provides an application of the OCA adhesive material or the preparation method in preparing an OCA adhesive film.
[0034] Compared with the prior art, the present invention has the following beneficial effects:
[0035] The OCA adhesive material provided by the present invention comprises components including an acrylic polymer. A chain transfer agent is added during the preparation of the acrylic polymer, and the molecular weight of the polymer is adjusted by reducing the chain length of the acrylic polymer. Meanwhile, the chain transfer agent contains double bonds which can be used as a cross-linking monomer, and is combined with a heat-induced free radical initiator to adjust the cross-linking degree of the OCA adhesive material. This is because when heated, the heat-induced free radical initiator generates free radicals which can open the double bonds in the monomer, thereby increasing the cross-linking degree. The OCA adhesive material provided by the present invention has high strength at room temperature and is not prone to overflowing, but has good fluidity and a high filling rate at high temperatures, and is superior in properties such as lamination, overflowing during coating, thermal disassembly integrity, die-cutting and embossing, and effectively solves the technical deficiencies in the use of the OCA adhesive film produced by the prior art. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0037] Figure 1 This is a schematic diagram of the structure of the OCA film provided by the present invention.
[0038] Icon: 100-OCA film layer; 200-light release film; 300-heavy release film. DETAILED DESCRIPTION
[0039] Unless otherwise defined herein, scientific and technical terms used in conjunction with the present invention shall have the meanings commonly understood by those of ordinary skill in the art. The meaning and scope of the terms should be clear, however, in the case of any potential ambiguity, the definitions provided herein take precedence over any dictionary or external definitions. In this application, unless otherwise stated, the use of "or" means "and / or". In addition, the use of the term "including" and other forms is non-limiting.
[0040] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0041] The first aspect of the present invention provides an OCA adhesive material, the components of which include an acrylic polymer and at least two components of an isocyanate curing agent, a functional monomer and a photoinitiator-type free radical initiator; wherein the components of the acrylic polymer include a reactive diluent monomer, an acrylic polar monomer, a chain transfer agent and a thermally initiated free radical initiator.
[0042] The OCA adhesive material provided by the present invention comprises components of an acrylic polymer. A chain transfer agent is added during the preparation of the acrylic polymer to reduce the chain length of the acrylic polymer so as to adjust the molecular weight of the polymer. Meanwhile, the chain transfer agent contains double bonds which can be used as a cross-linking monomer and is combined with a thermally induced free radical initiator to adjust the cross-linking degree of the OCA adhesive material. This is because when heated, the thermally induced free radical initiator generates free radicals which can open the double bonds in the monomer, thereby increasing the cross-linking degree. The OCA adhesive material provided by the present invention has high strength at room temperature and is not prone to overflowing, but has good fluidity and high filling rate at high temperature, and is superior in properties such as lamination, overflowing during coating, thermal disassembly integrity, die-cutting and embossing, and effectively solves the technical deficiencies in the use of the OCA adhesive film produced by the prior art.
[0043] In some preferred embodiments, the weight average molecular weight of the acrylic polymer is 10000-900000, preferably 50000-400000;
[0044] Preferably, the glass transition temperature of the acrylic polymer is in the range of -30 to 30°C, preferably -20 to 0°C;
[0045] Preferably, the shear strain rate (slope, the ratio of shear strain to time) of the acrylic polymer is in the range of 0.0010-0.60.
[0046] Preferably, the creep compliance of the acrylic polymer is in the range of 0.000001-0.001.
[0047] In the present invention, the acrylic polymer has a weight average molecular weight of 50,000-400,000 Daltons, and its glass transition temperature is in the range of -20-0°C. If it is higher than 0 degrees Celsius, the adhesion and filling properties of the acrylic polymer will be greatly affected. The slope (ratio of shear strain to time) of the acrylic polymer should be in the range of 0.001-0.6. If it is less than 0.001, the coating, bonding and overflow properties will be seriously affected.
[0048] In some preferred embodiments, the acrylic polymer comprises the following components by weight:
[0049] 60-80 parts of active diluent monomer, 10-40 parts of acrylic polar monomer, 0.01-5 parts of chain transfer agent and 0.1-5 parts of thermally initiated free radical initiator.
[0050] Wherein, in the acrylic polymer, the addition amount of the reactive diluent monomer is 60-80 parts, for example, it can be 60 parts, 65 parts, 70 parts, 75 parts, 80 parts, etc.;
[0051] Wherein, in the acrylic polymer, the addition amount of the acrylic polar monomer is 10-40 parts, for example, it can be 10 parts, 15 parts, 20 parts, 25 parts, 30 parts, 40 parts, etc.;
[0052] Wherein, in the acrylic polymer, the added amount of the chain transfer agent is 0.01-5 parts, for example, it can be 0.01 parts, 0.1 parts, 1 parts, 2 parts, 3 parts, 4 parts, 5 parts, etc.;
[0053] Wherein, in the acrylic polymer, the added amount of the thermally initiated free radical initiator is 0.1-5 parts, for example, it can be 0.1 parts, 1 parts, 2 parts, 3 parts, 4 parts, 5 parts, etc.
[0054] In some preferred embodiments, the chain transfer agent includes at least one of pentaerythritol triacrylate and dipentaerythritol hexaacrylate;
[0055] In the present invention, the preferred weight proportion of the chain transfer agent is between 0.01 and 5 parts. If it is less than 0.01, the degree of polymerization of the polymer will be too high. If it is greater than 5, the molecular weight distribution will be too wide, affecting its overflow performance.
[0056] Preferably, the acrylic polar monomer includes a monomer containing an amide group or a hydroxyl group, specifically including at least one of (meth)acrylamide, N-methyl(meth)acrylamide, N,N-dimethyl(meth)acrylamide, N,N-diethylaminoethyl(meth)acrylate, N,N-dimethylaminoethyl(meth)acrylamide, hydroxyethyl acrylate, and N-vinylcaprolactam;
[0057] In the present invention, the acrylic polar monomer has an amide bond at the other end of the acrylic acid, and the increase in its content can effectively adjust the molecular weight of the polymer and enhance the cohesive force. The preferred proportion is 10-40 parts. If it is less than 10 parts, the content of small molecules in the acrylic polymer is too high, the cohesive force is insufficient, and there is a risk of residual glue at high temperature. If it is more than 40 parts, the content of large molecules in the acrylic polymer is too much, resulting in a significant impact on its bonding and overflow performance.
[0058] Preferably, the reactive diluent monomer includes at least one of 2-ethylhexyl acrylate, lauryl acrylate, benzyl acrylate, isobornyl acrylate, tetrahydrofurfuryl acrylate, ethoxyethoxyethyl acrylate and allyl 2-ethylbutyrate;
[0059] In the present invention, within a certain range, the higher the content of the active diluent monomer, the greater the adhesion. The active diluent monomer has a longer carbon chain structure, which is conducive to the flow of molecules, thereby facilitating the polymer molecules to penetrate into the surface of the glass or steel plate to increase the adhesion. The preferred weight ratio is between 60 and 80 parts. If it is less than 60 parts, the filling effect of the final product is not good, and it is easy to have a back bubble phenomenon. If the ratio is greater than 80 parts, the colloid is too soft and the overflow effect is too strong, which will affect its bonding and overflow performance.
[0060] Preferably, the thermally initiated free radical initiator comprises at least one of azobisisobutyronitrile, azobisisoheptanenitrile and dibenzoyl peroxide.
[0061] In the present invention, the thermally initiated free radical initiator is preferably azobisisobutyronitrile, which is used to generate free radicals after heating in the first stage, which can open the double bonds in the monomer and start the polymerization reaction. The preferred weight ratio is between 0.001 and 5 parts. If it is less than 0.001 parts, the polymerization reaction may be terminated due to the high activation energy required in the polymerization deinitiation stage, resulting in more side reactions. If the thermally initiated free radical initiator is more than 5 parts, it is easy to cause implosion.
[0062] In some preferred embodiments, the acrylic polymer component further includes a solvent;
[0063] Preferably, the organic solvent used in the polymerization reaction includes at least one of toluene, ethyl acetate, n-butyl acetate, acetone, butanone, isophorone, cyclohexanone, methanol and isopropanol.
[0064] In some preferred embodiments, the OCA adhesive further comprises the following components by weight:
[0065] 100 parts of acrylic polymer, 0.01-3 parts of isocyanate curing agent, 0.0001-2 parts of functional monomer and 0.01-5 parts of photoinitiator free radical initiator.
[0066] Wherein, in the OCA adhesive, the amount of isocyanate curing agent added is 0.01-3 parts, for example, it can be 0.01 parts, 0.1 parts, 1 parts, 2 parts, 3 parts, etc.;
[0067] Wherein, in the OCA adhesive, the addition amount of the functional monomer is 0.0001-2 parts, for example, it can be 0.0001 parts, 0.001 parts, 0.01 parts, 0.1 parts, 1 parts, 2 parts, etc.;
[0068] Wherein, in the OCA adhesive, the amount of the photoinitiator added is 0.01-5 parts, for example, it can be 0.01 parts, 0.1 parts, 1 parts, 2 parts, 3 parts, 4 parts, 5 parts, etc.;
[0069] In some preferred embodiments, the isocyanate curing agent includes at least one of diphenylmethane diisocyanate, toluene diisocyanate, dicyclohexylmethane-4,4'-diisocyanate, tetramethyl-m-xylylene diisocyanate, isocyanoethyl (meth)acrylate and isocyanate ethyl acrylate;
[0070] Preferably, the functional monomer includes at least one of 1,6-hexanediol diacrylate, tripropylene glycol diacrylate, neopentyl glycol diacrylate, tricyclodecane dimethanol diacrylate, ethoxylated trimethylolpropane triacrylate, propoxylated glycerol triacrylate and trimethylolpropane triacrylate;
[0071] In the present invention, the functionality of the functional monomer plays an important role in affecting the crosslinking degree of the pressure-sensitive adhesive (i.e., OCA adhesive material). The value of the phase angle at 0.1HZ is used to characterize the crosslinking degree. Therefore, the functionality of the functional monomer and the effect of its addition amount on the crosslinking degree of the pressure-sensitive adhesive can be characterized in this way. The above monomers mainly play a role in adjusting the crosslinking degree of the acrylic polymer.
[0072] Preferably, the photoinitiator free radical initiator is at least one of 1-hydroxy-cyclohexyl-phenyl ketone, 2-methyl-2-(4-morpholinyl)-4'-(methylthio)propiophenone, а,а-dimethyl-а-phenylacetophenone, 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone and 1-hydroxycycloethylphenylacetone.
[0073] In the present invention, under the same irradiation dose, the gel fraction of the pressure-sensitive adhesive (i.e., OCA adhesive) decreases with the increase in the amount of photoinitiator added. The reason is that the more the initiator is added, the more free radicals are generated during curing, resulting in the occurrence of chain termination, thereby increasing the number of polymers with low relative molecular weight or polymers that do not participate in crosslinking, and reducing the gel content; as a preferred weight portion of the photoinitiator, if the proportion of the photoinitiator is less than 0.01 parts, the degree of crosslinking after polymerization is low, and the cohesive force is insufficient. If the proportion of the initiator is higher than 5 parts, the photoinitiator decomposes under UV light, increasing the content of small molecules in the adhesive film and affecting the overflow performance.
[0074] Further explanation, in the present invention, the highly active chain transfer agent pentaerythritol triacrylate is preferred. First, as a chain transfer agent, it reduces the activity of newly generated free radicals and reduces the chain length of the acrylic polymer to adjust the molecular weight of the polymer. It can effectively adjust the relative molecular mass and molecular weight distribution of the acrylic polymer at low concentrations. At the same time, the chain transfer agent contains three double bonds and can be used as a crosslinking monomer. Under the action of a thermally initiated free radical initiator, its double bonds are opened to increase the crosslinking degree of the acrylic polymer. More importantly, the chain transfer agent contains hydroxyl groups, which can be combined with an isocyanate curing agent in the second stage of preparing the OCA film to adjust the strength of the OCA film (specifically, when preparing the acrylic polymer, the chain transfer agent is added, and the hydroxyl group, double bond and other groups of the chain transfer agent are combined with the acrylic polymer, and the acrylic polymer is further combined with the isocyanate curing agent). The acrylic polymer is treated with a photoinitiator free radical initiator under 200-400nm UV light to prepare an OCA film. The acrylic polymer has a weight average molecular weight of 50000-400000 Daltons, a glass transition temperature within the range of -20-0°C, a slope (ratio of shear strain to time) of the acrylic polymer within the range of 0.010-0.50, and a phase angle of 10-85% at 120°C, a frequency of 0-30Hz, and a shear strain of 1%-10%. At the same time, the OCA adhesive has greater strength at 25°C and is not prone to overflow, while at high temperatures it has better fluidity and a higher filling rate, so that the OCA adhesive meets the industry's high standards in terms of lamination, coating overflow, thermal disassembly integrity, die-cutting and embossing, thereby obtaining an OCA film with excellent performance, effectively solving the technical deficiencies in the use of the OCA film produced by the prior art.
[0075] The second aspect of the present invention provides a method for preparing the OCA adhesive, comprising the following steps:
[0076] The acrylic polymer, isocyanate curing agent, functional monomer and photoinitiator free radical initiator in the formulated amount are mixed and then irradiated with ultraviolet light to prepare the OCA adhesive material.
[0077] In some preferred embodiments, the acrylic acid polymer is prepared by the following steps:
[0078] The acrylic polymer is prepared by mixing the reactive diluent monomer, the acrylic polar monomer, the chain transfer agent and the thermally initiated free radical initiator in the formulated amount.
[0079] In the present invention, the OCA adhesive is prepared by the following steps: mixing an acrylic polymer, a functional monomer, an isocyanate curing agent, and a photoinitiator-type free radical initiator according to weight parts, removing bubbles, and irradiating with 200-400nm UV light to obtain the OCA adhesive.
[0080] A third aspect of the present invention provides an application of the OCA adhesive material or the preparation method in preparing an OCA adhesive film.
[0081] in, Figure 1 Schematic diagram of the structure of an OCA film, which is used to prepare an OCA tape. The middle layer of the OCA tape is an OCA film layer 100 (i.e., the OCA film prepared by the present invention). The OCA film prepared by the present invention is a single-layer OCA film. The upper and lower sides of the OCA film layer 100 are respectively a light release film 200 (whose thickness is 50 μm) and a heavy release film 300 (whose thickness is 100 μm). The middle layer OCA film layer 100, the light release film 200, and the heavy release film 300 together constitute the OCA tape.
[0082] The present invention is further described below by way of examples. Unless otherwise specified, the materials in the examples are prepared according to existing methods or directly purchased from the market.
[0083] Example 1
[0084] This embodiment provides an OCA adhesive material, which includes the following components by weight:
[0085] 100 parts of acrylic polymer, 0.1 parts of ethyl isocyanate acrylate (AOI), 0.003 parts of trimethylolpropane triacrylate (TMPTA) and 0.23 parts of 2-methyl-2-(4-morpholinyl)-4'-(methylthio)propiophenone (907);
[0086] Wherein, the acrylic acid polymer comprises the following components by weight:
[0087] 35 parts of tetrahydrofurfuryl acrylate (THFA), 7 parts of allyl 2-ethylbutyrate (ALLYL 2-ETHYLBUTYRATE), 33 parts of ethoxyethoxyethyl acrylate (EOEOEA), 18 parts of N-vinyl caprolactam (NVCL), 7 parts of hydroxyethyl acrylate (HEA) and 0.1 parts of pentaerythritol triacrylate (PETA), solvent (50 parts of ethyl acetate, 50 parts of butanone) and 0.2 parts of azobisisobutyronitrile.
[0088] Example 2
[0089] This embodiment provides an OCA adhesive material, which includes the following components by weight:
[0090] 100 parts of acrylic polymer, 0.1 parts of ethyl isocyanate acrylate (AOI), 0.0035 parts of 1,6-hexanediol diacrylate (HDDA) and 0.34 parts of 1-hydroxycycloethylphenylacetone (184);
[0091] Wherein, the acrylic acid polymer comprises the following components by weight:
[0092] 35 parts of tetrahydrofurfuryl acrylate (THFA), 7 parts of allyl 2-ethylbutyrate (ALLYL 2-ETHYLBUTYRATE), 36 parts of ethoxyethoxyethyl acrylate (EOEOEA), 15 parts of N-vinyl caprolactam (NVCL), 7 parts of hydroxyethyl acrylate (HEA) and 0.1 parts of pentaerythritol triacrylate (PETA), solvent (50 parts of ethyl acetate, 50 parts of butanone) and 0.1 parts of azobisisobutyronitrile.
[0093] Example 3
[0094] This embodiment provides an OCA adhesive material, which includes the following components by weight:
[0095] 100 parts of acrylic polymer, 0.15 parts of ethyl isocyanate acrylate (AOI), 0.0025 parts of trimethylolpropane triacrylate (TMPTA) and 0.25 parts of 2-methyl-2-(4-morpholinyl)-4'-(methylthio)propiophenone (907);
[0096] Wherein, the acrylic acid polymer comprises the following components by weight:
[0097] 30 parts of tetrahydrofurfuryl acrylate (THFA), 8 parts of allyl 2-ethylbutyrate (ALLYL 2-ETHYLBUTYRATE), 41 parts of ethoxyethoxyethyl acrylate (EOEOEA), 12 parts of N-vinyl caprolactam (NVCL), 9 parts of hydroxyethyl acrylate (HEA) and 0.1 parts of pentaerythritol triacrylate (PETA), solvent (50 parts of ethyl acetate, 50 parts of butanone) and 0.16 parts of azobisisobutyronitrile.
[0098] Example 4
[0099] This embodiment provides an OCA adhesive material, which further comprises the following components by weight:
[0100] 100 parts of acrylic polymer, 0.1 parts of HDDA, 0.002 parts of 1,6-hexanediol diacrylate and 0.33 parts of 1-hydroxycycloethylphenylacetone (184);
[0101] Wherein, the acrylic acid polymer comprises the following components by weight:
[0102] 33 parts of tetrahydrofurfuryl acrylate (THFA), 9 parts of allyl 2-ethylbutyrate (ALLYL 2-ETHYLBUTYRATE), 35 parts of ethoxyethoxyethyl acrylate (EOEOEA), 12 parts of N-vinyl caprolactam (NVCL), 11 parts of hydroxyethyl acrylate (HEA) and 0.2 parts of pentaerythritol triacrylate (PETA), solvent (50 parts of ethyl acetate, 50 parts of butanone) and 0.3 parts of azobisisobutyronitrile.
[0103] Example 5
[0104] This embodiment provides an OCA adhesive material, which includes the following components by weight:
[0105] 100 parts of acrylic polymer, 0.1 parts of ethyl isocyanate acrylate (AOI), 0.001 parts of 1,6-hexanediol diacrylate (HDDA) and 0.35 parts of 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone (659);
[0106] Wherein, the acrylic acid polymer comprises the following components by weight:
[0107] 31 parts of tetrahydrofurfuryl acrylate (THFA), 12 parts of allyl 2-ethylbutyrate (ALLYL 2-ETHYLBUTYRATE), 33 parts of ethoxyethoxyethyl acrylate (EOEOEA), 9 parts of N-vinyl caprolactam (NVCL), 15 parts of hydroxyethyl acrylate (HEA) and 0.2 parts of pentaerythritol triacrylate (PETA), solvent (50 parts of ethyl acetate, 50 parts of butanone) and 0.3 parts of azobisisobutyronitrile.
[0108] Example 6
[0109] This embodiment provides an OCA adhesive material, which includes the following components by weight:
[0110] 100 parts of acrylic polymer, 0.1 parts of ethyl isocyanate acrylate (AOI), 0.0056 parts of 1,6-hexanediol diacrylate (HDDA) and 0.2 parts of 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone (659);
[0111] Wherein, the acrylic acid polymer comprises the following components by weight:
[0112] 31 parts of tetrahydrofurfuryl acrylate (THFA), 17 parts of allyl 2-ethylbutyrate (ALLYL 2-ETHYLBUTYRATE), 30 parts of ethoxyethoxyethyl acrylate (EOEOEA), 9 parts of N-vinyl caprolactam (NVCL), 3 parts of hydroxyethyl acrylate (HEA) and 0.2 parts of pentaerythritol triacrylate (PETA), solvent (50 parts of ethyl acetate, 50 parts of butanone) and 0.1 parts of azobisisobutyronitrile.
[0113] Example 7
[0114] This embodiment provides an OCA adhesive material, which includes the following components by weight:
[0115] 100 parts of acrylic polymer, 0.1 parts of ethyl isocyanate acrylate (AOI), 0.001 parts of trimethylolpropane triacrylate (TMPTA) and 0.45 parts of 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone (659);
[0116] Wherein, the acrylic acid polymer comprises the following components by weight:
[0117] Tetrahydrofurfuryl acrylate (THFA) THFA 33 parts, 2-ethylbutyric acid allyl ester (ALLYL 2-ETHYLBUTYRATE) 7 parts, ethoxyethoxyethyl acrylate (EOEOEA) 38 parts, N-vinyl caprolactam (NVCL) 15 parts, hydroxyethyl acrylate (HEA) 3 parts and 0.5 parts of pentaerythritol triacrylate (PETA), add 0.1 parts of azobisisobutyronitrile and solvent (50 parts of ethyl acetate, 50 parts of butanone).
[0118] Example 8
[0119] This embodiment provides an OCA adhesive material, which includes the following components by weight:
[0120] 100 parts of acrylic polymer, 0.1 parts of ethyl isocyanate acrylate (AOI), 0.001 parts of trimethylolpropane triacrylate (TMPTA) and 0.2 parts of 1-hydroxycycloethylphenylacetone (184);
[0121] Wherein, the acrylic acid polymer comprises the following components by weight:
[0122] 30 parts of tetrahydrofurfuryl acrylate (THFA), 9 parts of allyl 2-ethylbutyrate (ALLYL 2-ETHYLBUTYRATE), 33 parts of ethoxyethoxyethyl acrylate (EOEOEA), 15 parts of N-vinyl caprolactam (NVCL), 3 parts of hydroxyethyl acrylate (HEA), 0.1 parts of azobisisobutyronitrile, 0.7 parts of pentaerythritol triacrylate (PETA) and solvent (50 parts of ethyl acetate, 50 parts of butanone).
[0123] Example 9
[0124] This embodiment provides an OCA adhesive material, which includes the following components by weight:
[0125] 100 parts of acrylic polymer, 3 parts of ethyl isocyanate acrylate (AOI), 2 parts of 1,6-hexanediol diacrylate and 5 parts of 2-methyl-2-(4-morpholinyl)-4'-(methylthio)propiophenone (907);
[0126] Wherein, the acrylic acid polymer comprises the following components by weight:
[0127] 30 parts of tetrahydrofurfuryl acrylate (THFA), 5 parts of allyl 2-ethylbutyrate (ALLYL 2-ETHYLBUTYRATE), 25 parts of ethoxyethoxyethyl acrylate (EOEOEA), 20 parts of N-vinyl caprolactam (NVCL), 20 parts of hydroxyethyl acrylate (HEA) and 5 parts of pentaerythritol triacrylate (PETA), solvent (50 parts of ethyl acetate, 50 parts of butanone) and 0.1 parts of azobisisobutyronitrile.
[0128] Example 10
[0129] This embodiment provides an OCA adhesive material, which includes the following components by weight:
[0130] 100 parts of acrylic polymer, 0.01 parts of ethyl isocyanate acrylate (AOI), 0.0001 parts of 1,6-hexanediol diacrylate and 0.01 parts of 2-methyl-2-(4-morpholinyl)-4'-(methylthio)propiophenone (907);
[0131] Wherein, the acrylic acid polymer comprises the following components by weight:
[0132] 40 parts of tetrahydrofurfuryl acrylate (THFA), 10 parts of allyl 2-ethylbutyrate (ALLYL 2-ETHYLBUTYRATE), 30 parts of ethoxyethoxyethyl acrylate (EOEOEA), 5 parts of N-vinyl caprolactam (NVCL), 5 parts of hydroxyethyl acrylate (HEA) and 0.01 parts of pentaerythritol triacrylate (PETA), solvent (50 parts of ethyl acetate, 50 parts of butanone) and 3 parts of azobisisobutyronitrile.
[0133] Embodiment 11
[0134] This embodiment provides an OCA adhesive material, which includes the following components by weight:
[0135] 100 parts of acrylic polymer, 0.005 parts of ethyl isocyanate acrylate (AOI), 2.1 parts of 1,6-hexanediol diacrylate and 5.5 parts of 2-methyl-2-(4-morpholinyl)-4'-(methylthio)propiophenone (907);
[0136] Wherein, the acrylic acid polymer comprises the following components by weight:
[0137] 29 parts of tetrahydrofurfuryl acrylate (THFA), 5 parts of allyl 2-ethylbutyrate (ALLYL 2-ETHYLBUTYRATE), 25 parts of ethoxyethoxyethyl acrylate (EOEOEA), 5 parts of N-vinyl caprolactam (NVCL), 4 parts of hydroxyethyl acrylate (HEA) and 6 parts of pentaerythritol triacrylate (PETA), solvent (50 parts of ethyl acetate, 50 parts of butanone) and 0.05 parts of azobisisobutyronitrile.
[0138] Example 12
[0139] This embodiment provides an OCA adhesive material, which includes the following components by weight:
[0140] 100 parts of acrylic polymer, 3.1 parts of ethyl isocyanate acrylate (AOI), 0.00005 parts of 1,6-hexanediol diacrylate and 0.005 parts of 2-methyl-2-(4-morpholinyl)-4'-(methylthio)propiophenone (907);
[0141] Wherein, the acrylic acid polymer comprises the following components by weight:
[0142] 41 parts of tetrahydrofurfuryl acrylate (THFA), 10 parts of allyl 2-ethylbutyrate (ALLYL 2-ETHYLBUTYRATE), 30 parts of ethoxyethoxyethyl acrylate (EOEOEA), 21 parts of N-vinyl caprolactam (NVCL), 21 parts of hydroxyethyl acrylate (HEA), 0.005 parts of pentaerythritol triacrylate (PETA), solvent (50 parts of ethyl acetate, 50 parts of butanone), and 3.5 parts of azobisisobutyronitrile.
[0143] Application Example 1-12
[0144] Application Examples 1-12 provide an application of an OCA adhesive material in preparing an OCA adhesive film. The OCA adhesive material components in Examples 1-12 are respectively used. The specific preparation process of the OCA adhesive film is as follows:
[0145] (1) Weighing the formulated amount of reactive diluent monomer, acrylic acid polar monomer, chain transfer agent and remaining solvent (50 parts of ethyl acetate and 50 parts of butanone), mixing them evenly, first deoxygenating with nitrogen for 1 hour, then slowly heating to 75° C., adding thermally initiated free radical initiator, and performing bulk polymerization under nitrogen protection. After the reaction is complete, keeping the temperature at 80° C. for 5 hours to obtain acrylic acid polymer, and measuring its weight average molecular weight;
[0146] (2) Take 100 parts of the above acrylic polymer, add isocyanate curing agent, functional monomer and thermal free radical initiator, stir thoroughly to remove bubbles, apply glue on 50um PET release film, put it in a 60℃ oven to dry for 30 minutes, and laminate 100um PET heavy release film on the release surface; put it in a 90℃ oven to cure for 48h, and use UV to cure to obtain an OCA film. The thickness of the obtained OCA film is 180um.
[0147] Comparative Example 1
[0148] This comparative example provides an OCA adhesive material, the components of which differ from those of Example 1 in that no chain transfer agent is contained. The remaining components are the same as those of Example 1.
[0149] Comparative application example 1
[0150] This comparative application example provides an application of an OCA adhesive material in preparing an OCA adhesive film. The OCA adhesive material components in Comparative Example 1 are used, and the preparation process of the OCA adhesive film is consistent with the steps of Application Example 1.
[0151] Test samples: The OCA films prepared in Application Examples 1-12 and the OCA films prepared in Comparative Application Example 1 were used as samples.
[0152] Test method: The samples were tested for glue overflow, die cutting and stamping, filling and thermal disassembly integrity. The test results are shown in Table 1, which also includes the component formulas of Examples 1-12 and Comparative Example 1.
[0153] The test method for glue overflow is: put 50 die-cut products in a 45℃ oven for 48 hours, and then observe the glue overflow at the edge of each piece under a microscope. If the glue overflow distance does not exceed 0.01mm, it is OK; if it exceeds 0.01mm, it is NG; the test method for die-cutting and embossing is: observe the distance between the die-cut edge and the glue overflow under a microscope. If it is less than 0.01, it is OK; if it is greater than 0.01, it is NG;
[0154] The filling test method is: stick the die-cut OCA on the polarizer, use a vacuum laminator to stick the OCA with a 25um ink step, place it at 50℃ and 0.4MPa for 30min, if there are no bubbles, it is OK, if there are bubbles, it is NG;
[0155] The thermal disassembly integrity test method is: after attaching the OCA to the cover plate, adsorb it on the heating platform. Use a 0.06m diamond wire to cut into the OCA glue layer, move the diamond wire back and forth to cut the OCA glue layer three times, open the OCA, and if the OCA remains intact on a certain layer, it means OK and NG.
[0156] Table 1
[0157]
[0158]
[0159]
[0160]
[0161] It can be seen from the data of Application Example 1 and Comparative Application Example 1 that when no chain transfer agent is added, the performance of the product is poor in all aspects; it can be seen from Application Examples 6-9 of the present invention that increasing the proportion of chain transfer agent added when preparing acrylic polymer can reduce the molecular weight of acrylic polymer, reduce the crosslinking degree of acrylic polymer (increase in 0.1Hz value), reduce the gel fraction, increase the slope value, and thus enhance the overflow and filling performance of OCA film. When the molecular weight is 5-40W, the product is superior in coating overflow, thermal disassembly integrity, die cutting and embossing and other performances.
[0162] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. An OCA adhesive material, characterized in that: The components include acrylic polymer, and at least two components selected from the group consisting of isocyanate curing agent, functional monomer and photoinitiator free radical initiator; The components of the acrylic polymer include reactive diluent monomers, acrylic polar monomers, chain transfer agents and thermally initiated free radical initiators.
2. The OCA adhesive material according to claim 1, characterized in that: The weight average molecular weight of the acrylic polymer is 10,000-900,000, preferably 50,000-400,000; Preferably, the glass transition temperature of the acrylic polymer is -30 to 30°C, preferably -20 to 0°C; Preferably, the shear strain rate of the acrylic polymer is 0.0010-0.60; Preferably, the creep compliance of the acrylic polymer is 0.000001-0.
001.
3. The OCA adhesive material according to claim 1, characterized in that: The acrylic polymer comprises the following components by weight: 60-80 parts of active diluent monomer, 10-40 parts of acrylic polar monomer, 0.01-5 parts of chain transfer agent and 0.1-5 parts of thermally initiated free radical initiator.
4. The OCA adhesive material according to claim 3, characterized in that: The chain transfer agent includes at least one of pentaerythritol triacrylate and dipentaerythritol hexaacrylate; Preferably, the acrylic polar monomer includes at least one of (meth)acrylamide, N-methyl(meth)acrylamide, N,N-dimethyl(meth)acrylamide, N,N-diethylaminoethyl(meth)acrylate, N,N-dimethylaminoethyl(meth)acrylamide, hydroxyethyl acrylate and N-vinylcaprolactam; Preferably, the reactive diluent monomer includes at least one of 2-ethylhexyl acrylate, lauryl acrylate, benzyl acrylate, isobornyl acrylate, tetrahydrofurfuryl acrylate, ethoxyethoxyethyl acrylate and allyl 2-ethylbutyrate; Preferably, the thermally initiated free radical initiator includes at least one of azobisisobutyronitrile and azobisisoheptanenitrile.
5. The OCA adhesive material according to claim 3, characterized in that: The components of the acrylic polymer also include a solvent; Preferably, the solvent comprises at least one of toluene, ethyl acetate, n-butyl acetate, acetone, butanone, isophorone, cyclohexanone, methanol and isopropanol.
6. The OCA adhesive material according to claim 1, characterized in that: The OCA adhesive material further comprises the following components by weight: 100 parts of acrylic polymer, 0.01-3 parts of isocyanate curing agent, 0.0001-2 parts of functional monomer and 0.01-5 parts of photoinitiator free radical initiator.
7. The OCA adhesive material according to claim 6, characterized in that: The isocyanate curing agent includes at least one of diphenylmethane diisocyanate, toluene diisocyanate, dicyclohexylmethane-4,4'-diisocyanate, tetramethyl-m-xylylene diisocyanate, isocyanoethyl (meth)acrylate and isocyanate ethyl acrylate; Preferably, the functional monomer includes at least one of 1,6-hexanediol diacrylate, tripropylene glycol diacrylate, neopentyl glycol diacrylate, tricyclodecane dimethanol diacrylate, ethoxylated trimethylolpropane triacrylate, propoxylated glycerol triacrylate and trimethylolpropane triacrylate; Preferably, the photoinitiator free radical initiator is at least one of 1-hydroxy-cyclohexyl-phenyl ketone, 2-methyl-2-(4-morpholinyl)-4'-(methylthio)propiophenone, а,а-dimethyl-а-phenylacetophenone, 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone and 1-hydroxycycloethylphenylacetone.
8. The method for preparing the OCA adhesive material according to any one of claims 1 to 7, characterized in that: The following steps are involved: The acrylic polymer, isocyanate curing agent, functional monomer and photoinitiator free radical initiator in the formulated amount are mixed and then irradiated with ultraviolet light to prepare the OCA adhesive material.
9. The preparation method according to claim 8, characterized in that: The acrylic acid polymer is prepared by the following steps: The acrylic polymer is prepared by mixing the reactive diluent monomer, the acrylic polar monomer, the chain transfer agent and the thermally initiated free radical initiator in the formulated amount.
10. Use of the OCA adhesive material according to any one of claims 1 to 7 or the preparation method according to claim 8 or 9 in preparing an OCA adhesive film.